Behind embassy walls : the life and times of an American diplomat - Grove, Brandon, 1929- (University of Missouri Press, 2005)
"Autobiography of American diplomat Brandon Grove's career in the U.S. Foreign Service through the Cold War, McCarthyism, and Somalia crisis. Includes assessments of Chester Bowles; George Herbert Walker Bush; Robert Kennedy; George Kennan; Omar Torrijos; John Sherman Cooper; Philip Habib; Willy Brandt; Mobutu; Vernon Walters; Jimmy Carter; and Ronald Reagan"--Provided by publisher.